RI 2982 Method For Comparison Of The Size Of Materials Used In Blast-Furnace Burdens ? Importance Of Knowing Size Of Materials Charged - S. P. Kinney (The National Institute for Occupational Safety and Health (NIOSH), 1930)
[The blast-furnace operator is often confronted with the problem of determining the size of the materials which are used in the furnace burden. The statement is heard that the coke is larger or smaller or that certain ore is finer than that previously used. A screen analysis of the materials used gives a measure of the different sizes of materials in an aggregate. When one is fine and the other is coarse, the difference is obvious; but when the materials are of similar sire, it is more difficult to estimate the degree of finances or coarseness. In considering raw materials it would be desirable to be able to judge the size of the radio ideal materials entering the furnace and the burden as a whole, by one representative value, such as the average size of particle. Previous work by Perrott and Kinney3 developed a method for measuring the average size of particle in a mass of finely ground materials, and an attempt will be made to apply this method to the materials included in the blast-furnace charge and to the entire burden.]